Imagens digitais aplicadas no estudo da análise multitemporal do uso e ocupação do solo numa microbacia - Campos, Sergio [UNESP]; Gobbi, Talita Teixeira Azevedo [UNESP]; Reche, Aline Minarelli [UNESP] (ANAP - Associacao Amigos de Natureza de Alta Paulista, 2014)
The knowledge of the soil occupation as for his nature, location, occurrence form, changes happened in certain periods, they are valuable for the programming of activities that you seek to the development agricultural, economical and social of the area. This work aimed at to identify and to quantify the soil occupation of Stream Petiço Watershed - Botucatu (SP), through the Geographical Information System IDRISI and data of sensor Landsat 5 TM of 09/06/97 and 23/08/2013. For the analysis of the results it was verified that the eucalyptus culture, due to existence of great reforestation companies in the watershed, together with the native forests they are predominant in the study area, the remaining of the area is occupied by pastures and soil prepared for the planting of agricultural cultures.

El conocimiento del uso de la tierra en la naturaleza, ubicación, forma deocurrencia, los cambios en ciertos períodos, son muy útiles para la programación de actividades orientadas al desarrollo agrícola, económico y social de la región. Este estudio tuvo como objetivo identificar y cuantificar la Cuenca de la ocupación del suelode Petiço Stream - Botucatu (SP) a través del Sistema de Información GeográficaIDRISI y datos del sensor Landsat 5 TM 06/09/97 y 08/23/2013. Los resultadosencontraron que el cultivo de eucalipto, debido a la existencia de grandes empresas de reforestación en la cuenca, junto con los bosques son predominantes en el área de estudio, el resto de la superficie está ocupada por pastos y tierra preparada para la siembra de cultivos.

O conhecimento da ocupação do solo quanto à sua natureza, localização, forma de ocorrência, mudanças ocorridas em determinados períodos, são de grande valia para a programação de atividades que visam ao desenvolvimento agrícola, econômico e social da região. Este trabalho objetivou identificar e quantificar a ocupação de solo da Microbacia do Córrego Petiço – Botucatu (SP), através do Sistema de Informações Geográficas IDRISI e dados do sensor Landsat 5 TM de 09/06/97 e 23/08/2013. Os resultados constataram-se que a cultura de eucalipto, devido a existência de grandes empresas reflorestadoras na microbacia, juntamente com as florestas são predominantes na área de estudo, o restante da área é ocupada por pastagens e solo preparado para o plantio de culturas agrícolas.
Digital images applied in the study of multitemporal analysis use and occupation of soil in a watershed
Imágenes digitales aplicadas en el estudio de uso análisis multitemporal y ocupación del suelo en una cuenca
Keywords: Occupation; Soil; Cultures; Reforestation; Ocupación del suelo; Las plantas; La reforestación; Ocupação do solo; Culturas; Reflorestamento